2023
DOI: 10.1101/2023.01.23.525135
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Charting the Heterogeneity of Colorectal Cancer Consensus Molecular Subtypes using Spatial Transcriptomics

Abstract: The heterogeneity of colorectal cancer (CRC) contributes to substantial differences in patient response to standard therapies. The consensus molecular subtypes (CMS) of CRC is the most widely-used gene expression-based classification and has contributed to a better understanding of disease heterogeneity and prognosis. Nevertheless, CMS intratumoral heterogeneity restricts its clinical application, stressing the necessity of further characterizing the composition and architecture of CRC. Here, we used Spatial T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 114 publications
1
10
0
Order By: Relevance
“…Among desert-enriched genes, we retrieved the glucose transported GLUT10 (encoded by SLC2A10 ) and the Wnt pathway inhibitor NKD1, which showed preferential expression in tumor cells and fibroblasts ( figures 5B –D and supplemental figure S5B ). By using publicly available spatial transcriptomics data in CRC (Valdeolivas et al 2023 44 and Wu et al 2022 43 ), we confirmed an enrichment in NKD1 expression in CD8-desert as compared with CD8-high tumor areas. In addition, we observed the strongest expression of LAMP5 in the sample showing CD8 infiltration in the stromal area only, in line with LAMP5 being excluded-enriched ( supplemental figure S5C ).…”
Section: Resultssupporting
confidence: 64%
“…Among desert-enriched genes, we retrieved the glucose transported GLUT10 (encoded by SLC2A10 ) and the Wnt pathway inhibitor NKD1, which showed preferential expression in tumor cells and fibroblasts ( figures 5B –D and supplemental figure S5B ). By using publicly available spatial transcriptomics data in CRC (Valdeolivas et al 2023 44 and Wu et al 2022 43 ), we confirmed an enrichment in NKD1 expression in CD8-desert as compared with CD8-high tumor areas. In addition, we observed the strongest expression of LAMP5 in the sample showing CD8 infiltration in the stromal area only, in line with LAMP5 being excluded-enriched ( supplemental figure S5C ).…”
Section: Resultssupporting
confidence: 64%
“…We thus undertook comprehensive simulation experiments on existing fully digitized clinical cohorts to capture the morphology related to transcriptional CMS calls and to address whether clinically established sampling protocols are sufficient to describe tumour heterogeneity at the gene-expression level. As expected and due to the spatially heterogeneous nature of CRC tumours [30,31], our results suggest that sampling less than five tumour biopsies is not sufficient to properly predict the CMS call that would be obtained from an equivalent resection specimen of the same tumour. Our results corroborate the 2021 ESGE recommendation as our experiments show on two independent external test datasets of 147 and 266 patients, that five or more standard tumorous biopsy fragments are sufficient to reliably capture the global tumour phenotype needed to achieve CMS classification performance with fidelity close to full resection specimens.…”
Section: Discussionmentioning
confidence: 56%
“…Color visualization is based on the highest voted tile-level predicted imCMS class among the five trained models that form the ensemble model of experiment [E3a] as indicated in the bottom-right legend. Classification maps illustrate the spatially resolved imCMS calls across biopsy samples including samples with some level of pervasive heterogeneity as previously described for both image-based as well as molecular analysis methods [13, 33, 34]. …”
Section: Supplementary Materials and Methodsmentioning
confidence: 99%
“…Kasumi representations can easily be adapted to explore tissue-specific common and differential patterns between conditions, even beyond association to clinical features. Furthermore, while we considered view compositions capturing a single spatial context, Kasumi can be deployed with more complex compositions addressing different spatial and functional contexts and different omics technologies [34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%